Correlation Between Maternal Serum Concentrations of Mannose-Binding Lectin and The Risk of Shorter Duration of Pregnancy and Lower Birth Weight (Texas Journal of Medical Science, 2022)
The aim of this study is to investigate whether serum concentrations of MBL correlate with the incidence of preterm birth and low birth weight in a cohort of women with signs of threatened preterm birth